PENERAPAN SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA TOKO BESI LESTARI SUBUR - Anjani, Isabella; Solikah, Mar’atus; Andy, Kurniawan (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Inventory is vulnerable to damage or theft, for this reason it is necessary to have internal inventory control aimed at protecting information about inventory more reliably. Internal control must be implemented effectively to prevent errors, fraud, and fraud. This study aims to determine the suitability of the implementation of the internal control system for merchandise inventory at the Lestari Subur Iron Shop. The research method used is descriptive method with a qualitative approach. The research was conducted using observation, interview, and documentation methods. The results of this study indicate that the implementation of an internal control system for merchandise inventory at the Lestari Subur Iron Shop according to the COSO component is not working properly, because there is no separation of duties and authorities. In addition, information and communication that are not in accordance with the results of orders are repeated, there is a buildup of stock in the warehouse. The risk assessment experienced is caused by stock differences caused by incorrect input of names or quantities of incoming and outgoing goods, as well as damage to goods caused by quite hard movements during the delivery process from suppliers.